2014
DOI: 10.1021/nn5058968
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of a Single-Domain Hexagonal Boron Nitride Monolayer

Abstract: We investigate the structure of epitaxially grown hexagonal boron nitride (h-BN) on Ir(111) by chemical vapor deposition of borazine. Using photoelectron diffraction spectroscopy, we unambiguously show that a single-domain h-BN monolayer can be synthesized by a cyclic dose of high-purity borazine onto the metal substrate at room temperature followed by annealing at T=1270 K, this method giving rise to a diffraction pattern with 3-fold symmetry. In contrast, high-temperature borazine deposition (T=1070 K) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 45 publications
2
74
3
Order By: Relevance
“…2(f). Note that the existence of mirror domains does not necessarily imply an equal distribution of domain types and even single domain orientations can be achieved in similar systems, depending on the growth conditions [28]. Based on the observed circular dichroism here, we conclude that the domain distribution is not equal in the present case.…”
Section: Diffmentioning
confidence: 56%
“…2(f). Note that the existence of mirror domains does not necessarily imply an equal distribution of domain types and even single domain orientations can be achieved in similar systems, depending on the growth conditions [28]. Based on the observed circular dichroism here, we conclude that the domain distribution is not equal in the present case.…”
Section: Diffmentioning
confidence: 56%
“…Moreover, Auwärter et al revealed that the ratio of R‐0 and R‐60 structures on Ni (111) could be modulated by pretreating the Ni substrates, but the deep mechanism is unclear . Besides, through changing the precursor dosing manner, h‐BN of unique orientation can be grown on Ir (111) substrate . Only R‐60 h‐BN domains grow on Ir (111) by dosing borazine at low temperature and subsequent high temperature annealing, but R‐60 and R‐0 domains coexist if borazine is dosed directly at high‐temperature .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…Besides, through changing the precursor dosing manner, h‐BN of unique orientation can be grown on Ir (111) substrate . Only R‐60 h‐BN domains grow on Ir (111) by dosing borazine at low temperature and subsequent high temperature annealing, but R‐60 and R‐0 domains coexist if borazine is dosed directly at high‐temperature . The R‐60 structure is also commonly found on Rh (111) and Ru (0001), where h‐BN monolayers are bonded on these surfaces much more strongly .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…Besides exfoliation, chemical vapor deposition on catalytically active metals is a way to prepare well-defined monolayers [13]. Examples are epitaxial h-BN layers on Rh(111) [14][15][16], Ru(0001) [17][18][19], Pt(111) [20], and Ir(111) [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%